2013
DOI: 10.4161/cc.26814
|View full text |Cite
|
Sign up to set email alerts
|

USP3 counteracts RNF168 via deubiquitinating H2A and γH2AX at lysine 13 and 15

Abstract: A Wani (2014) USP3 counteracts RNF168 via deubiquitinating H2A and γH2AX at lysine 13 and 15, Cell Cycle, 13:1, 106-114,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(102 citation statements)
references
References 34 publications
2
100
0
Order By: Relevance
“…40 Accordingly, we wondered whether expressing a ubiquitin-histone H2AX fusion protein in cells deficient for RNF8 or RNF168 would rescue 53BP1 recruitment to IR-induced foci (IRIF). We first examined RNF8-/-mouse embryo fibroblasts (MEFs).…”
Section: Resultsmentioning
confidence: 99%
“…40 Accordingly, we wondered whether expressing a ubiquitin-histone H2AX fusion protein in cells deficient for RNF8 or RNF168 would rescue 53BP1 recruitment to IR-induced foci (IRIF). We first examined RNF8-/-mouse embryo fibroblasts (MEFs).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple deubiquitinating enzymes were proposed to remove monomeric ubiquitin from K119 and K13/K15 of H2A and therefore it is likely that there is some redundancy in controlling histone deubiquitination. [52][53][54] Among these deubiquitinating enzymes USP3 and USP16 were reported to be regulated by mitotic events. USP3 associates with the chromatin and has the ability to deubiquitinate both K119 and K13/K15 of H2A.…”
Section: Discussionmentioning
confidence: 99%
“…USP3, USP16, and USP51 function distinctly in response to IR-induced DNA breaks Previous studies have shown that two other DUBs, USP3 and USP16, are also involved in DDR (Nicassio et al 2007;Lancini et al 2014;Sharma et al 2014). It is known that USP16 targets H2AK119ub and H2AK15ub and that USP3 targets H2AK15ub (Sharma et al 2014;Zhang et al 2014).…”
Section: Usp51 Functions Downstream From Mdc1 Recruitment In Responsementioning
confidence: 99%
“…It is known that USP16 targets H2AK119ub and H2AK15ub and that USP3 targets H2AK15ub (Sharma et al 2014;Zhang et al 2014). To gain insight into how USP51 functions in DDR, we compared the effect of overexpression of USP3, USP16, and USP51 on the formation of IR-induced 53BP1 and RNF168 foci.…”
Section: Usp51 Functions Downstream From Mdc1 Recruitment In Responsementioning
confidence: 99%
See 1 more Smart Citation